Photoelastic analysis of forces generated by T-loop springs made with stainless steel or titanium-molybdenum alloy - Martins Maia, Luiz Guilherme [UNESP]; de Moraes Maia, Mila Leite; Monini, Andre da Costa [UNESP]; Vianna, Alexandre Protasio [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP] (Mosby-elsevier, 2011)
Introduction: The purpose of this study was to use photoelastic analysis to compare the system of forces generated by retraction T-loop springs made with stainless steel and titanium-molybdenum alloy (TMA) (Ormco, Glendora, Calif) with photoelastic analysis. Methods: Three photoelastic models were used to evaluate retraction T-loop springs with the same preactivations in 2 groups. In group 1, the loop was constructed with a stainless steel wire, and 2 helicoids were incorporated on top of the T-loop; in group 2, it was made with TMA and no helicoids. Results: Upon using the qualitative analysis of the fringe order in the photoelastic model, it was observed that the magnitude of force generated by the springs in group 1 was significantly higher than that in group 2. However, both had symmetry for the active and reactive units related to the system of force. Conclusions: Both springs had the same mechanical characteristics. TMA springs showed lower force levels. (Am J Orthod Dentofacial Orthop 2011;140:e123-e128)